A Survey of Perceptions of Consulting in Inclusive Preschool Classrooms. Issue 1 (January 2023) - Forsythe, Natalie; Larson, Anne L.
Abstract : This study examined consultants' and consultees' perspectives of itinerant service delivery for students with disabilities in inclusive preschool classrooms. Consultants (i.e., early childhood special education teachers and related service providers) and consultees (lead and assistant preschool teachers) working in inclusive preschool classrooms in a large Mountain West school district completed a survey eliciting their perceptions on consulting, including their definitions of the consulting role and factors they believed to be most important in building successful consulting relationships. Participants' answers to survey questions were analyzed and grouped into themes. There were similarities across both groups when describing the role of consultants, including assumptions that consultants should work directly with students in the classroom. Consultants and consultees also agreed that they have positive relationships with one another and that consultants are effective; however, consultant and consultee survey responses emphasized a need for respect within the consulting relationship. Understanding perceptions of consultative approaches may lead to practices and policies that improve consultative services and potentially lead to improved outcomes for preschool children with disabilities in inclusive settings.